2020
DOI: 10.1002/jgm.3282
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit umbilical cord mesenchymal stem cells: A new option for tissue engineering

Abstract: BackgroundThe source and availability of cells for tissue engineering in large scale research or clinical trials requires special attention. We propose the idea of applying rabbit umbilical cord mesenchymal stem cells for this purpose.MethodsHere, the structure of the rabbit umbilical cord was analyzed and compared to that of human umbilical cord, both macroscopically and histologically. Next, we isolated, cultured and identified the proliferative activity and immunological characteristics of rabbit umbilical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Some researchers have paid attention to the rabbit for its docile character and high-reproductive rate. Li et al [ 9 ] has isolated umbilical cord mesenchymal stem cells (MSCs) from rabbits to repair murine bone defects by tissue engineering[ 9 ]. Considering the strong reproductive capacity, short reproductive cycle, and sufficient species-specific reagents of rodents[ 17 ], there is a possibility of using rodents as a xenogeneic stem cell transplantation source.…”
Section: Sources Of Xenogeneic Stem Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers have paid attention to the rabbit for its docile character and high-reproductive rate. Li et al [ 9 ] has isolated umbilical cord mesenchymal stem cells (MSCs) from rabbits to repair murine bone defects by tissue engineering[ 9 ]. Considering the strong reproductive capacity, short reproductive cycle, and sufficient species-specific reagents of rodents[ 17 ], there is a possibility of using rodents as a xenogeneic stem cell transplantation source.…”
Section: Sources Of Xenogeneic Stem Cellsmentioning
confidence: 99%
“…MSCs have been regarded as the most ideal cell type on account of their extensive cell sources, lack of ethical restrictions for its use, easy accessibility without invasiveness, high survivability in in vivo conditions, low-immunological characteristics, low tumorigenicity, and high safety in clinical applications[ 18 - 22 ]. Many research studies have demonstrated that xenogeneic MSC transplantation is effective in the treatment of liver failure, myocardial infarction, and bone defects[ 9 , 12 , 13 ]. ESCs have also gained attention with their totipotency and high-self-renewal capacity[ 10 ].…”
Section: Sources Of Xenogeneic Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations